2019
DOI: 10.1002/ags3.12280
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes after sentinel node navigation surgery for early gastric cancer

Abstract: Aim This study evaluated the prognosis after sentinel node navigation surgery (SNNS) for early gastric cancer. Methods For 100 patients who underwent SNNS (between August 13, 2003 and December 17, 2018) at our hospital, the survival outcomes were investigated. Results (a) SN were detected with a diagnostic accuracy of 0.98. (b) Of seven patients who had positive SN metastasis, three underwent standard gastrectomy with D2 lymph node dissection. Among them, one patient died of recurrence (bone) and the other two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Although there are only a few retrospective studies with small sample sizes, the prognosis of patients treated with SNNS has been reported to be good, with a 5-year overall survival rate of 98.0–98.5% [ 69 , 70 , 71 ]. SNNS may be oncologically safe in EGC, but we need to wait for the results of ongoing Japanese and Korean trials.…”
Section: Sentinel Node Navigation Surgerymentioning
confidence: 99%
“…Although there are only a few retrospective studies with small sample sizes, the prognosis of patients treated with SNNS has been reported to be good, with a 5-year overall survival rate of 98.0–98.5% [ 69 , 70 , 71 ]. SNNS may be oncologically safe in EGC, but we need to wait for the results of ongoing Japanese and Korean trials.…”
Section: Sentinel Node Navigation Surgerymentioning
confidence: 99%
“…The 3‐year overall and relapse‐free survival for laparoscopic sentinel node navigation surgery is similar to those of standard gastrectomy in early gastric cancer patients 30 . Several studies have shown a comparable 5‐year survival, as well as better quality of life 31‐33 . On the basis of these results, a prospective multicenter trial to assess the survival outcomes and patients' quality of life is underway.…”
Section: Current Evidence Supporting Lgmentioning
confidence: 84%
“…30 Several studies have shown a comparable 5-year survival, as well as better quality of life. [31][32][33] On the basis of these results, a prospective multicenter trial to assess the survival outcomes and patients' quality of life is underway. Additionally, a multicenter prospective trial to evaluate the feasibility of sentinel node navigation surgery after endoscopic submucosal dissection (SENORITA 2 trial) is ongoing and expected to contribute to the evolution of surgical practice in patients with early gastric cancer.…”
Section: Sentinel Node Navigation Surgerymentioning
confidence: 99%
“…However, they concluded that SNNS could be an alternative if rescue surgery is appropriately performed; this was supported by 3‐year overall survival (OS) and disease‐specific survival that were equivalent to those of conventional surgery. In Japan, a single‐center study demonstrated a satisfactory 5‐year survival rate of 98.5%, in addition to a better quality of life as measured by a validated quality of life scale called the PGSAS‐45 17,18 . Currently, a multicenter triple‐arm confirmatory study that has been approved by the Japanese authority is under investigation and the result is expected to be available in several years 19 …”
Section: Surgical Management Of Gastric Cancermentioning
confidence: 99%